Sustainable rural development indicators in awarded rural properties in Marechal Cândido Rondon, Paraná, Brazil - Hein, André Fernando (2019)
Family farming is not a homogeneous block of farmers, as it is composed of different profiles of farmers, depending on the size of the property, access to technology, profitability, capitalization, among others. It can be classified into Subsistence (AFS), Transition (AFT), and Consolidated (AFC) Family Farming. Given other studies that analyze sustainability in AFS, this study aims to evaluate the Sustainable Rural Development (DRS) in AFC, having as a sample award-winning farmers in the municipality of Marechal Cândido Rondon, Parana. These producers were found to have good DRS indicators and the indicators: technical assistance, profitability, family succession and dependence on resources from other activities were discrepant from the results of studies with AFS.